EVALUASI TEOLOGIS PANDANGAN KARL BARTH TENTANG PENYATAAN UMUM - Made Nopen Supriadi (Manna Rafflesia, 2019)
Humans know God because God reveals himself. The Bible records two ways that God revealed Himself, namely through general revelation and special revelation. God has established public revelations through the means of the universe, conscience and history, so that through these means humans realize the existence of a divine and authoritative person. However, a theologian named Karl Barth rejects the existence of a general statement to be able to know God. Therefore through this paper we will explain general revelation and theological evaluation of Karl Barth's views on public revelation.